A masculinidade e o autocuidado dos homens usuários do SUS no contexto da atenção primária à saúde – uma revisão integrativa - DEMETERI, Matheus Alves (2023)
Introduction: although the Article 196 of the Federal Constitution of 1988 guarantees health as a right of all citizens and it is the duty of the State to ensure it, men have always been on the margins of public health policies in Brazil. Only nineteen years after the creation of SUS was a policy specifically aimed at the male population instituted, the National Policy for Integral Attention to Men's Health. Although this policy was created to give more relevance to men's health, men still live shorter lives and die earlier from preventable causes than women, and are more vulnerable to chronic diseases, severe conditions, and violence. Although the health problems of the male gender are linked to the biological condition, such pictures have their beginning and end in the social question. Objective: to understand the relationship of men who use the SUS with their aspects of self-care in the context of Primary Health Care. Methodology: this is an integrative literature review conducted in the Virtual Health Library database, using controlled descriptors in health sciences: self-care; men's health; culture; masculinity; health services; gender and health; men; national policy for integral attention to men's health. Results and discussion: of the 581 articles found in the database used, after using the inclusion and exclusion criteria, we were left with 10 articles that make up the sample field of this integrative review. After a thorough reading of these articles, three categories of analysis emerged: (1) society and male behavior, (2) the SUS and assistance to the male public, and (3) male behavior, self-care and Primary Health Care. A topic was created regarding the possibilities of Occupational Therapy in men's health, considering self-care as an activity of daily living that is part of the areas of occupational performance of the human being. Conclusion: the social construction of masculinity presented as a standard to be followed, negatively influences male self-care and the search for health services, especially in Primary Care.